Predictable Movements in Yen/DM Exchange Rates - Kong, Janet (IMF Working Papers; Working Paper ;, 2000)
This paper examines the relevance of PPP, the adjustment channel of real exchange rate and the predictability of the movement in nominal exchange rate by studying the behavior of yen/DM exchange rate, using cointegration method. Results support PPP and find that the real exchange rate is mean-reverting. The change in the nominal exchange rate exhibits significant auto-regressive property. These findings imply that movements in the nominal yen/DM exchange rate is actually predictable. The error-correction model and a simple first order autoregressive model both outperform the random walk model in out-of-sample forecasting.